Устойчивость пластины с трещиной при неоднородном докритическом состоянии - Коханенко, Е.Ю. (Видавничий дім "Академперіодика" НАН України, 2007)
The plane problem of stability of a rectangular plate with central crack under uniaxial compressing of end-walls is considered. Conditions of fixing the end–walls correspond, in integral form, to conditions of a hinge unit. The approximate solution of the problems of elasticity and stability are obtained by the variation-difference method. The example of calculation of critical parameters is given.